A newly recognized syndrome involving limbs, pelvis, and genital organs or a variant of Al-Awadi/Raas-Rothschild syndrome? - Piranit N. Kantaputra (2018)
We report on a 3-year-old Thai boy with limb, pelvic, and genital malformations. The combination of findings found in this patient is similar to that of Al-Awadi/Raas-Rothchild syndrome (AARRS) or limb/pelvis hypoplasia/aplasia syndrome. The upper limbs are more severely affected than the lower ones. Unlike that of AARRS, the radial ray is more severely affected than the ulnar ray. The presence of humeroulnar synostosis and humero-ulnar-radial synostosis and the absence of a radius distinguishes it from AARRS. The similarities and dissimilarities between the features in the present patient and other limb-pelvic hypoplasia/aplasia syndromes are discussed. The findings in this group of patients appear to demonstrate limb-pelvis-genital organ developmental field defects. © 2004 Wiley-Liss, Inc.